Method of increasing the dynamic exactness of co-ordinate measuring machines drives - Квасніков, В.П.; Осмоловський, О.І. (Proceedings of National Aviation University (archive), 2005)
An analysis of the requirements set to the control drives of co-ordinate measuring machines is conducted. A new structure of the drive’s regulator is offered, which enables a substantial increase of dynamic characteristics and exactness of the co-ordinate measuring machines drives. In a mathematical model the operation of ordinary and offered control systems is compared for different laws of the input influence.